COMPARATIVE ANALYSIS OF STANDARDISED AND NON-STANDARDISED MICROSCOPY METHODS OF URINE SEDIMENTS - Drochnerytė, Agnė; Sabaliauskienė, Zita (PROFESSIONAL STUDIES: Theory And Practice, 2022)
The aim of the study – to compare standardised and non-standardised methods of urine sediment microscopy. The study included 40 urine samples with increased erythrocyte and/or leukocyte and/or protein levels as compared with recommended normal values detected by chemical analysis method and additional 20 urine samples which chemical analysis did not reveal any pathological changes. All 60 samples were tested applying a standardised and non-standardised sediment microscopy analysis.